1989
DOI: 10.1111/j.1939-1676.1989.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia Associated With Acute Bovine Virus Diarrhea Infection in Cattle

Abstract: Thrombocytopenia was observed in 15 of 146 cases of clinically acute bovine viral diarrhea virus (BVDV) infection in adult cattle. Platelet counts ranged from 2,000 to 33,000/~1. Clinically, a bleeding tendency was manifested by bloody diarrhea, petechial and ecchymotic hemorrhage, epistaxis, and abnormal bleeding from injection sites. Coagulation testing (six cases) gave no evidence of disseminated intravascular coagulation. Bone marrow aspirates were suggestive of active marrow necrosis (two cases) or recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 10 publications
1
69
0
1
Order By: Relevance
“…at day 12 PE). Nevertheless hemorrhage, which has previously been associated with acute BVDV type 2 infections [8,24], was not a predominant pathological feature in our study as well as in the study reported by others using the same BVDV isolate [11]. Moreover, gross and histological lesions in the alimentary tract, as observed especially in animals more than 6 months of age during the outbreaks of BVDV infection in Ontario in 1993 [7], and from where the 24515 BVDV isolate was isolated, were not a predominant finding in our 4 to 4.5 month-old calves, as previously noted for calves less than 6 months of age [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…at day 12 PE). Nevertheless hemorrhage, which has previously been associated with acute BVDV type 2 infections [8,24], was not a predominant pathological feature in our study as well as in the study reported by others using the same BVDV isolate [11]. Moreover, gross and histological lesions in the alimentary tract, as observed especially in animals more than 6 months of age during the outbreaks of BVDV infection in Ontario in 1993 [7], and from where the 24515 BVDV isolate was isolated, were not a predominant finding in our 4 to 4.5 month-old calves, as previously noted for calves less than 6 months of age [7].…”
Section: Discussionmentioning
confidence: 99%
“…Serious clinical conditions characterized by thrombocytopenia and hemorrhages have been observed in calves infected with BVDV isolates in the late 1980's [8,24]. More recently, severe acute outbreaks of BVDV-associated disease in young and adult cattle have been documented in Northeastern United States [21] and in the provinces of Québec [13,22] and Ontario [7] in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to these initial reports, descriptions that followed pointed to acute uncomplicated BVDV as a mild or sub-clinical disease of short duration with negligible mortality in all ages of cattle [1-2, 9, 10]. During the past two decades clinically severe disease outbreaks associated with acute BVDV infection have been reported in the US, Britain, Canada and Germany [11,12,18,24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, severe thrombocytopenia and hemorrhagic disease have been described in some herd epidemics (Corapi et al, 1989;Rebhun et al, 1989;Carman et al, 1998). Preliminary studies demonstrated that the isolates associated with these outbreaks were genetically and antigenically distinct from the classical BVDV strains.…”
Section: Introductionmentioning
confidence: 96%